Comparison of the general co-expression landscapes between human and mouse. (14th March 2017) - Liu, Di; Zhao, Linna; Chen, Yang; Wang, Zhaoyang; Xu, Jing; Li, Ying; Lei, Changgui; Hu, Simeng; Niu, Miaomiao; Jiang, Yongshuai
Abstract: The murine model serves as an important experimental system in biomedical science because of its high degree of similarities at the sequence level with human. Recent studies have compared the transcriptional landscapes between human and mouse, but the general co-expression landscapes have not been characterized. Here, we calculated the general co-expression coefficients and constructed the general co-expression maps for human and mouse. The differences and similarities of the general co-expression maps between the two species were compared in detail. The results showed low similarities in the human and mouse, with only about 36.54% of the co-expression relationships conserved between the two species. These results indicate that researchers should pay attention to these differences when performing research using the expression data of human and mouse. To facilitate use of this information, we also developed the human–mouse general co-expression difference database (coexpressMAP) to search differences in co-expression between human and mouse. This database is freely available at http://www.bioapp.org/coexpressMAP .